Peny Penyortiran, Preservasi dan Identifikasi Keong Darat dari Hutan Pekarangan Kedungsalam -Malang di Museum Zoologicum Bogoriense Cibinong - Bogor - Irsyad, Fia Lutfiatul Hamidatul (Jurnal Sains dan Pendidikan Biologi, 2022)
Many efforts have been made by researchers to maintain natural wealth in Indonesia, one of which is by storing them in museums, before being stored there are several processes that must be carried out such as sorting, preservation and identification. Sorting land snails is important to find micro land snails, while preservation is a technique for processing land snails before they are identified. Identification is the process of naming the type of specimen found. Sorting, preservation and identification activities carried out in the Malacology laboratory of the Zoologicum Bogoriense Museum, Cibinong, resulted in a collection of and knowing the diversity of land snails from the agroforestry of Kedungsalam - Malang. A total of 5 L of soil and litter samples per plot from 9 plots from the agroforestry of Kedungsalam - Malang on June 16, 2014 to July 18 2014. From the sorting results, 132 specimens were identified, consisting of 11 species, including 7 macro snails, namely Lisschatina fulica, Amphidromus furcilatus, Bradybaena similaris, Cyclophorus rafflesi rafflesi, Elaphroconcha javacensis, Landouria rotatoria, Leptopoma vitreum, and 5 micro snails namely Liardetia sp., Microcystina sp., Subulina sp. and Succinea sp